2002
DOI: 10.1161/01.cir.0000016642.15031.34
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Predicts Sudden Death in Patients With Chronic Heart Failure

Abstract: Background-Given the high incidence of sudden death in patients with chronic heart failure (CHF) and the efficacy of implantable cardioverter-defibrillators, an appropriate tool for the prediction of sudden death is desirable. B-type natriuretic peptide (BNP) has prognostic significance in CHF, and the stimuli for its production cause electrophysiological abnormalities. This study tests BNP levels as a predictor of sudden death. Methods and Results-BNP levels, in addition to other neurohormonal, clinical, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
348
5
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(386 citation statements)
references
References 49 publications
18
348
5
15
Order By: Relevance
“…Our study extends these prior findings by demonstrating that, at baseline, 24 h and 72 h, NT-proBNP predicts adverse events independent Other studies have demonstrated that BNP predicts adverse events, particularly sudden cardiac death, in both the postmyocardial infarction (19) and heart failure populations (20). One potential clinical application of natriuretic peptides, yet to be tested, is to stratify patients according to their sudden cardiac death risk and to identify, together with other clinical variables, who may benefit from implantation of a cardioverter defibrillator.…”
Section: Prognosissupporting
confidence: 85%
“…Our study extends these prior findings by demonstrating that, at baseline, 24 h and 72 h, NT-proBNP predicts adverse events independent Other studies have demonstrated that BNP predicts adverse events, particularly sudden cardiac death, in both the postmyocardial infarction (19) and heart failure populations (20). One potential clinical application of natriuretic peptides, yet to be tested, is to stratify patients according to their sudden cardiac death risk and to identify, together with other clinical variables, who may benefit from implantation of a cardioverter defibrillator.…”
Section: Prognosissupporting
confidence: 85%
“…Although increased plasma levels of IL-6, 4 -7 TNF-α, 7,17 CRP 8 -10 and BNP 12,13 are all correlated with increased mortality in patients with chronic HF, the current study revealed that plasma levels of IL-6, TNF-α, CRP or BNP were not predictive of ventricular tachyarrhythmias in patients with moderate to severe systolic LV dysfunction.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to these biomarkers, brain natriuretic peptide (BNP), released by ventricular cardiomyocytes in response to myocardial tension and increased intravascular volume, was consistently shown to predict poor outcome 6,11 including sudden death 12,13 among HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…B‐type natriuretic peptide (BNP) and N‐terminal prohormone B‐type natriuretic peptide (NT‐proBNP) levels are well established predictors of HF hospitalization and mortality in patients with HF 4, 5, 6, 7. However, as the incidences of outcomes differ between patients with HF8 and patients with a recent ACS9 in a stable phase, it is less established how natriuretic peptides are associated with cardiovascular outcomes, especially subsequent MI and stroke, in the latter population 3, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%